A COMPARATIVE STUDY TO ASSESS SAFETY AND EFFICACY OF VILDAGLIPTIN AND METFORMIN WITH GLIMEPIRIDE AND METFORMIN AMONG TYPE 2 DIABETES PATIENTS - Ahmed, Ibrar; Ali, Zafar; Abdur Rahman Afridi, Muhammad; Ali, Sobia Sabir; Nawaz, Mohammad; Ghaffar, Tahir (Journal of Postgraduate Medical Institute, 2021)
Objective: To assess the safety and efficacy of Vildagliptin with metformin and Glimepiride with metformin among Type 2 Diabetes Mellitus (T2DM) patients with inadequate glycemic control using Metformin mono-therapy. Methodology: This comparative, interventional study was conducted at the Medicine and Endocrinology Department, Lady Reading Hospital, Peshawar. A total of 180 T2DM patients were divided into two groups (Glimepiride-Metformin group and Vildagliptin-Metformin group), with 90 patients in each group. Glycosylated hemoglobin (HbA1c), Fasting Plasma Glucose (FPG), Postprandial Glucose (PPG) were assessed with hypoglycemic incidences, weight gain, other adverse drug reactions were also monitored. The 1st follow-up visit was planned after 12-weeks of receiving the treatment and the 2nd after 24-weeks. Recorded data was analyzed through SPSS v.22.0. Results: The mean decrease in the FPG level after 24-weeks of treatment was -42.93±13.46 mg/dl in Vildagliptin-Metformin group, while it was. -46.76±11.04 mg/dl in the Glimepiride-Metformin group. Similarly, both drugs, Vildagliptin-Metformin vs Glimepiride-Metformin decreased mean PPG and HbA1c level i.e., -42.93 mg/dl vs. -46.76 mg/dl and -3.12% vs. -2.39% respectively (p<0.05). Mild adverse effects, like hypoglycemic incidences (10%) and weight gain (73.31±13.94 kg at 2nd visit) was more prominent among the Glimepiride-Metformin group. Conclusion: In terms of safety and efficacy, the Vildagliptin-Metformin combination showed a considerably healthier response in achieving the HbA1c level among T2DM patients, with no weight gain and decreased risk of hypoglycemia as compared to Glimepiride.